(3ebGQHI ShSjhJfehjIs - (3SYGO(B, (3fhQGdOjfs ((3HjQhJ(B:s (3OGQ Gdefgd GddHfGfj(B,s, 2010)
(3eaghe GdJfejI h JWhQ GdGbJUGO GddHfGfj , eYWjGJ h eDSSSGJ dHfGf GdLfhHj , hGbY GdbWGYGJ GdGbJUGOjI h GdGLJeGYjI aj dHfGf h dHfGf GdLfhHj , CKQ GdGhVGY GdGbJUGOjI h GdGLJeGYjI aj dHfGf h dHfGf GdLfhHj aj GdChVGY GdOjeZQGajI (B( (3GdfRhM h GdgLQI h GdJgLjQ(B).s
(3eQGLY U(B.655 (3; LOGhd U(B.679 (3; edMb GdNQGFW h GdQShe GdHjGfjI U(B.687s
Keywords: (3GdJfejIs; (3GdOjehZQGajGs; (3GdScGfs; (3dHfGfs